Understanding and Using Health Experiences : Improving patient care - Ziebland, Sue; Coulter, Angela; Calabrese, Joseph D.; Locock, Louise (Oxford : Oxford University Press, 2013)
Improving patient experience is a global priority for health policy-makers and care providers. This book critically examines the various ways in which people's experience of health and healthcare can be recorded, analysed and therefore improved.
Formerly CIP.
Keywords: Medical care -- Evaluation